Lack of the Actin Capping Protein, Eps8, Affects NMDA-Type Glutamate Receptor Function and Composition - Morini, Raffaella; Ferrara, Silvia; Perrucci, Fabio; Zambetti, Stefania; Pelucchi, Silvia; Marcello, Elena; Gardoni, Fabrizio; Antonucci, Flavia; Matteoli, Michela; Menna, Elisabetta (Frontiers in Molecular Neuroscience, 2018)
Actin-based remodelling underlines spine morphogenesis and plasticity and is crucially involved in the processes that constantly reshape the circuitry of the adult brain in response to external stimuli, leading to learning and memory formation and supporting cognitive functions. Hence spine morphology and synaptic strength are tightly linked and indeed abnormalities in spine number and morphology have been described in a number of neurological disorders such as autism spectrum disorders (ASD), schizophrenia and intellectual disabilities. We have recently demonstrated that the actin regulating protein, Eps8, is essential for spine growth and long term potentiation. Indeed, mice lacking Eps8 display immature filopodia-like spines, which are unable to undergo potentiation, and are impaired in cognitive functions. Furthermore, reduced levels of Eps8 have been found in the brain of a cohort of patients affected by ASD compared to controls. Here we investigated whether the lack of Eps8, which is also part of the NMDA receptor complex, affects the functional maturation of the postsynaptic compartment. Our results demonstrate that Eps8 KO neurons display altered synaptic expression and subunit composition of NMDA receptors (i.e. increased GluN2B-, decreased GluN2A-containing receptors) and impaired GluN2B to GluN2A subunit shift. Indeed Eps8 KO neurons display increased content of GluN2B containing NMDA receptors both at the synaptic and extrasynaptic level. Furthermore, Eps8 KO neurons display an increased content of extra-synaptic GluN2B- containing receptors, suggesting that also the synaptic targeting of NMDA receptors is affected by the lack of Eps8. These data demonstrate that, besides regulation of spine morphogenesis, Eps8 also regulates the synaptic balance of NMDA receptors subunits GluN2A and GluN2B.